Mass Contacts Behaviour of rice growers under Seed Village Programme in District Baramulla (J&K) - K., Naresh; Veenita Kumari (Journal of Agricultural Extension Management, 2025)
The participation and the extent to which they used the mass contact methods in sharing their knowledge and experience of rice growers under seed village programme was conducted in five purposively selected Divisions of Baramulla district, which have the Seed Village Program under the rice crop. Data was personally collected by researcher through well-structured interview schedule. The majority of rice growers having medium level of mass contact were in sub-division Tangmarg (83.33%), followed by sub-division Sopore (68.90%), sub-division Pattan (68.57%), sub-division Rohamma (65.00%) and sub-division Baramulla (61.64%). However, the overall mass contact of the rice growers (67.42%) from all the five sub-divisions had medium level of mass contact.